2022
DOI: 10.1002/app.53064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization g‐C3N4‐doped PMMA polymeric nanocomposites films for electronic and optoelectronic applications

Abstract: Solution casting was used to synthesis polymethyl methacrylate (PMMA) nanocomposites with graphitic carbon nitride (g‐C3N4) nanoparticles in various percentages (0.033, 0.166, 0.33, 1.665, and 3.3 wt%). XRD patterns confirmed the amorphous nature of PMMA/C3N4 nanocomposites. Optical constants are obtained at room temperature in the 200–2500 nm wavelength range. The optical band gaps of PMMA/C3N4 doped films, both direct and indirect, are measured and have values change from 4.8 to 2.32 eV for Enormalgind and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…To this end, prepared samples of nanocomposites of TiO 2 NPs doped in the host blend of PVA:SA were examined for their utility in the optical limiting of CUT-OFF laser filters utilizing a continuous He-Ne laser working at 632.2 nm. In this study, the aperture Z-scan characteristics can be used to measure the prepared samples' nonlinear influence power magnitudes in watts per area [112]. The synthesized nanocomposites' output influence power and their normalized influence power are shown against the percentage of TiO 2 , as shown in Figure 13, where the normalized power was represented as the equivalent ratio between input influence power and output influence power.…”
Section: Optical Limiting Effectivenessmentioning
confidence: 99%
“…To this end, prepared samples of nanocomposites of TiO 2 NPs doped in the host blend of PVA:SA were examined for their utility in the optical limiting of CUT-OFF laser filters utilizing a continuous He-Ne laser working at 632.2 nm. In this study, the aperture Z-scan characteristics can be used to measure the prepared samples' nonlinear influence power magnitudes in watts per area [112]. The synthesized nanocomposites' output influence power and their normalized influence power are shown against the percentage of TiO 2 , as shown in Figure 13, where the normalized power was represented as the equivalent ratio between input influence power and output influence power.…”
Section: Optical Limiting Effectivenessmentioning
confidence: 99%
“…PMMA has diffraction peaks of and , this is the polymer's crystalline phase. Mervat I Muhammed et al, estimated the diffraction peaks of PMMA at comparable values (Muhammed et al 2022). The 1st-peak shape represents that extended polymer chains have been packed, while the 2nd-peak showed that the major chains had been ordered with gradually decreasing in their intensity (Rathika et al 2018).…”
Section: Structural and Properties Of The Polymeric Nanocomposite Lms...mentioning
confidence: 99%
“…6a, as the wavelength gets longer, the extinction coe cient rises, suggesting that the fraction of light lost due to scattering rises as well. The rise in the amount of V 2 O 5 NP content attributable to the rise in the absorbent portion of incident light is increased, and therefore, the energy loss occurs (Muhammed et al 2022).…”
Section: Optical Characterizationmentioning
confidence: 99%